Assessing the effect of agricultural land abandonment on bird communities in southern-eastern Europe - Zakkak, Sylvia; Radovic, Andreja; Nikolov, Stoyan C; Shumka, Spase; Kakalis, Lefteris; Kati, Vassiliki (Journal of environmental management, 2015)
Agricultural land abandonment is recognized as a major environmental threat in Europe, being particularly pronounced in south-eastern Europe, where knowledge on its effects is limited. Taking the Balkan Peninsula as a case study, we investigated agricultural abandonment impact on passerine communities at regional level. We set up a standard methodology for site selection (70 sites) and data collection, along a well-defined forest-encroachment gradient that reflects land abandonment in four countries: Albania, Bulgaria, Croatia and Greece. Regardless the different socio-economic and political histories in the Balkans that led to diverse land abandonment patterns in space and time, rural abandonment had a consistent negative effect on bird communities, while regional-level analysis revealed patterns that were hidden at local level. The general trends were an increase of forest-dwelling bird species at the expense of farmland birds, the decline of overall bird species richness, as well as the decline of Species of European Conservation Concern (SPECs) richness and abundance. Many farmland bird species declined with land abandonment, whereas few forest species benefited from the process. In conclusion, our results support CAP towards hampering rural land abandonment and preserving semi-open rural mosaics in remote upland areas, using a suite of management measures carefully tailored to local needs. The maintenance of traditional rural landscapes should be prioritized in the Balkans, through the timely identification of HNV farmland that is most prone to abandonment. We also suggest that coordinated transnational research is needed, for a better assessment of conservation options in remote rural landscapes at European scale, including the enhancement of wild grazers' populations as an alternative in areas where traditional land management is rather unlikely to be re-established.
Keywords: Croatia; Bulharsko; biodiverzita; Agriculture; Conservation of Natural Resources; Europe; Europe, Eastern; Evropa; zemědělství; Passerine birds; Albania; Forest encroachment; Birds; Chorvatsko; Řecko; Albánie; Conservation policy; východní Evropa; zachování přírodních zdrojů; zvířata; Bulgaria; lesy; Environment; Greece; Balkans; Biodiversity; životní prostředí; High nature value farmland; ptáci; Rural abandonment; Forests; Animals